Analisis Kemampuan Berpikir Kritis Dalam Memecahkan Masalah Matematika Ditinjau dari Disposisi Matematis Siswa Kelas VIII SMP PANCASILA - Rika Rika; Hodiyanto Hodiyanto; Wandra Irvandi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Abstract: This study aims to describe students’ critical thinking skills in solving mathematical problems in terms of their mathematical disposition. The study employs four indicators of critical thinking skills: interpretation, analysis, evaluation, and inference. This research uses a qualitative method with data collected through a mathematical disposition questionnaire, a critical thinking skills test, and interviews. Data analysis includes data reduction, data presentation, data presentation, and conclusion drawing. The results indicate that students with a high level of mathematical disposition show strength in initial interpretation but still have significant weaknesses in advanced analysis, evaluation, and inference. This suggests that although a high mathematical disposition supports initial understanding, the development of comprehensive critical thinking skills requires learning that emphasizes reflection, evaluation, and self-regulation. Keywords: Critical Thinking, Problem Solving, Mathematical Disposition